Continuity of Cognitive Change across Adulthood - Salthouse, Timothy A. (Psychon Bull Rev, 2016)
Although cross-sectional (between-person) comparisons consistently reveal age-related cognitive declines beginning in early adulthood, significant declines in longitudinal (within-person) comparisons are often not apparent until age 60 or later. These latter results have led to inferences that cognitive change does not begin until late middle age. However, because mean change reflects a mixture of maturational and experiential influences whose contributions could vary with age, it is important to examine other properties of change before reaching conclusions about the relation of age to cognitive change. The current study examined measures of stability, variability, and reliability of change, as well as correlations of changes in memory with changes in speed in 2,330 adults between 18 and 80 years of age. Despite substantial power to detect small effects, the absence of significant age differences in these properties suggests that cognitive change represents a qualitatively similar phenomenon across a large range of adulthood.